2019
DOI: 10.1063/1.5120397
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical etching of AlGaN for the realization of thin-film devices

Abstract: Heterogeneously integrated AlGaN epitaxial layers will be essential for future optical and electrical devices like thin-film flip-chip ultraviolet (UV) light-emitting diodes, UV vertical-cavity surface-emitting lasers, and high-electron mobility transistors on efficient heat sinks. Such AlGaN-membranes will also enable flexible and micromechanical devices. However, to develop a method to separate the AlGaN-device membranes from the substrate has proven to be challenging, in particular, for high-quality device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“… 29 31 An alternative way to remove the substrate is to use Al-content- and doping-selective electrochemical etching of AlGaN, which has recently been demonstrated by our groups. 32 , 33 This method allows for the fabrication of AlGaN membranes with high Al content, smooth surfaces, and well-defined thicknesses. Owing to these properties, the membranes can be used for a wide variety of thin-film devices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 29 31 An alternative way to remove the substrate is to use Al-content- and doping-selective electrochemical etching of AlGaN, which has recently been demonstrated by our groups. 32 , 33 This method allows for the fabrication of AlGaN membranes with high Al content, smooth surfaces, and well-defined thicknesses. Owing to these properties, the membranes can be used for a wide variety of thin-film devices.…”
mentioning
confidence: 99%
“…On a larger scale, the electrochemically etched surface has an inverted topography of that of the as-grown surface, similar to what we have reported previously. 32 The smooth etching was achieved by using a multilayered sacrificial layer, which promotes etching at the sacrificial layer and cavity interface; see Figure 1 d. This design enables incorporation of layers with lower Al content without degrading the crystal quality of the device layers, and the built-in polarization field yields sheets of high carrier concentrations, both of which enhance the etch selectivity 32 and result in smoother surfaces.…”
mentioning
confidence: 99%
“…Recently, we have demonstrated that electrochemical etching can be applied to etch AlGaN with an Al content up to 50%. 25 This opens up the possibility to incorporate a lattice matched sacrificial AlGaN layer that can be selectively removed to realize TFFC UV LEDs of high quality. In this work, we demonstrate a TFFC ultraviolet B (UVB) LED using this method.…”
mentioning
confidence: 99%
“…An etching voltage of 25 V vs the Ag/AgCl reference electrode was chosen to achieve complete removal of the n-doped Al 0:37 Ga 0:63 N sacrificial layer, as shown in Ref. 25, and still to prevent etching of the etch stop and doped device layers. The lower Al composition and higher doping of the sacrificial layer relative to the etch block layers on both the sides confine the etching to only the sacrificial layer.…”
mentioning
confidence: 99%
See 1 more Smart Citation